(untitled) (Fiep Bulletin - online, 2020)
INTRODUCTION: The NGO KRISTHAL is made up of volunteer beauticians who provide therapeutic care in order to promote health, well-being and quality of life for women. The Quick Massage technique consists of manipulating the main stress points of the body, providing relaxation, immediate relief from tension, physical and mental tiredness, being able to reduce stress with the application of 15 minutes of massage. Reflex Hand Massage aims to normalize body functions, decrease tension, improve nerve function and blood flow throughout the body. OBJECTIVE: To verify the impact of the application of adapted Quick Massage and Reflex Manual Massage on hospital staff through the NGO KRISTHAL. METHODOLOGY: Qualitative with the application of adapted Quick Massage and Manual Reflex Massage in female employees, between 28 and 69 years old, in a session held at Instituto Dante Pazzanese de Cardiologia. The procedure was performed through the reception of the volunteer, then sent to perform manual therapies, lasting 15 minutes for each therapy, after the service was answered a questionnaire. The sample consisted of 58 employees. RESULTS: From this sample it was possible to attend 58 women from different areas of practice within the hospital environment and it was found that 97% of the volunteers recognized the importance of having a NGO that aims to promote women’s quality of life, and 100% of the volunteers. approved the quality and effectiveness of our service. All participants reported relief from muscle tension, body relaxation, feeling of increased physical and mental disposition. CONCLUSION: We conclude that the creation of the NGO KRISTHAL and the area of ??aesthetics has its relevance in promoting women’s health and quality of life.